Narrative aftershocks: Digital retellings of an earthquake in Emilia-Romagna, Northern Italy. (October 2018) - Perrino, Sabina
Highlights: Rapid circulation of earthquake "counter-narratives" in two Italian blogs. Digital emphasis on environmental exploitation rather than victims' suffering/losses. Analysis of blogs as narratives-as-practices vs. narratives-as-texts. Analysis of interactional dynamics between bloggers and commenters in blogs. (Co)construction/solidification of antagonistic collective politicized identities. Abstract: This article focuses on the rapid diffusion of traumatic digital storytelling after a lethal earthquake damaged many towns across the northern Italian region of Emilia-Romagna in May 2012. This natural disaster produced a large amount of online narratives by and about the survivors and their family members and acquaintances. Through an analysis of the interactional dynamics between these storytellers and their commenters in blogs, this article explores how these traumatic stories can be reshaped and manipulated for different ends and how a politicized collective identity among bloggers and commenters can be (co)constructed, contested, and solidified through blogging. More specifically, this article shows how these digital counter-narratives attempt to transform an allegedly sympathy-based virtual community into a community enraged by the purported causes of all the widespread suffering and distress. In this way, these virtual communities' emotional stances are redirected more to environmental politics than to sympathy and grief in interesting ways. Besides investigating the pragmatics of narrative interaction in virtual environments, this article extends linguistic anthropological analytical and methodological tools to digital discursive practices.